2014
DOI: 10.1650/condor-14-7.1
|View full text |Cite
|
Sign up to set email alerts
|

Predator exclosures, predator removal, and habitat improvement increase nest success of Snowy Plovers in Oregon, USA

Abstract: Management to increase reproductive success is commonly used to aid recovery of threatened and endangered species. The Western Snowy Plover (Charadrius nivosus nivosus) breeds from coastal Washington, USA, to Baja California, Mexico, and in disjunct interior sites. The Pacific coast population is federally listed as Threatened; habitat loss and nest loss to a suite of terrestrial and avian predators are thought to be primary factors limiting population growth in this species. In coastal Oregon, USA, a consorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Dinsmore et al. () found that nest survival rates for the closely related snowy plover ( C. nivosus ) benefited from exclosures or predator removal, but that using both provided little added value for nest survival. Mayer and Ryan () found that electric fencing of breeding areas greatly improved nest and chick survival at sites in the Great Plains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dinsmore et al. () found that nest survival rates for the closely related snowy plover ( C. nivosus ) benefited from exclosures or predator removal, but that using both provided little added value for nest survival. Mayer and Ryan () found that electric fencing of breeding areas greatly improved nest and chick survival at sites in the Great Plains.…”
Section: Discussionmentioning
confidence: 99%
“…, Maslo and Lockwood , Dinsmore et al. ). However, problems associated with exclosures included nest abandonment, adult mortalities, and depredation of multiple exclosed nests at a site within a very short period of time (Vaske et al.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, beachgrass removal has recreated open nesting habitat and remains essential for plover productivity and recovery ( Fig. 9A; USFWS 1993, 2007, Muir and Colwell 2010, Zarnetske et al 2010, Dinsmore et al 2014, Pearson et al 2016.…”
Section: Shared Drivers: Plover-coastal Protection Tradeoffmentioning
confidence: 99%
“…mini-exclosures are also used, even though at some sites they have increased depredation on incubating adults and fledglings (neuman et al 2004). These problems, however, have not arisen at other sites (Dinsmore et al 2014). Between 2005 and 2016 four of these enclosures were installed at malibu lagoon state Beach, santa monica Beach, and Dockweiler state Beach.…”
mentioning
confidence: 99%